THU0535 NATURE AND IMPACT OF THE FRENCH NETWORK RESRIP ON SCHOOLING, FOR CHILDREN WITH CHRONIC INFLAMMATORY RHEUMATISM. (June 2019) - Dusser, Perrine; Hascoet, Chrystelle; Koné-Paut, Isabelle; Rossi-Semerano, Linda
Abstract : Background: Pediatric chronic inflammatory rheumatism (CIR) has a significant impact on daily life, especially on schooling, that can lead to child's drop-out. In this context, a French paediatric health network, RESRIP (Réseau pour les Rhumatismes Inflammatoires Pédiatriques), has been created in 2014 for children with CIR and living in the Ile-de-France region. Patients are included in this network if they meet certain criteria such as the need to find trained health professionals close to their home or for support because of adverse social conditions or difficulties with their schooling. If the criteria are fulfilled, the patient and his family participate in an intake interview which allows RESRIP to understand the patient's need and to set up targeted actions. Objectives: In our study, we aim to describe and evaluate RESRIP's role on improving school attendance and tackling absenteeism Methods: A descriptive retrospective study was performed regarding the support provided by RESRIP with respect to patients' schooling and education professionals. Rates of non-attendance were collected at inclusion and every 6 months from 2014 to 2017, through a standardized auto-questionnaire. Results: 278 patients (M/F: 0.29) aged 12.7 years on average (± 4.9, range 2-21) were taken care of between 2014 and 2017 by RESRIP. Juvenile idiopathic arthritis (JIA) (n = 142), connective tissue disease (n = 49) and auto-inflammatory disease (AID) (n = 32) are the 3 main pathologies covered. Among the 278 patients, twenty-one percent of patients needed academic support when entering the network, including: 37% in the JIA group, 34% in the connective tissue group and 18% in the AID group. Educational assistance was set up for all patients with school difficulties at inclusion but also for all the patients during their follow-up. Patient Support: 178 Individual Action Plan (IAP) were implemented by RESRIP. Twelve patients benefited from additional time for their school exams and 10 were allowed to pass the baccalaureat (French final college exam) over two years instead of a year. In thirty patients, sports education has been adapted. Forty-one MDPH files (Departmental Houses for the Disabled) were produced to enable the establishment of a school life assistant (AVS), teaching materials and/or technical aids. Finally, 8 patients received home schooling assistance through Home Learning Assistance Services (SAPAD). Education professional support: RERSIP established partnerships with the French National Education (FNE) and the SAPAD (home tuition service for ill children). For the FNE, RESRIP provided school doctors or nurses with: 8 continuing medical training and 25 personal interviews to explain the pathologies. In addition, 5 multidisciplinary meetings, within the institutions were organized, for 5 patients with social integration difficulties and stigmatization. RESRIP actions, has allowed a significant decrease in school absenteeism between 2014 and 2017: 3.2 days per year on average at day 1 to 0.5 days per year on average (p <0.05) at 42 months. Conclusion: Over time, a better understanding of the impact of chronic illness over school and education professionals, has allowed RERSIP to improve its support. The result is a notable decline in school absenteeism and in unjustified physical education exemptions. Several projects are underway: The development of a standard IAP available for doctors, the set-up of a partnership with hospital school, willing to help for the implementation of home school support courses in addition to SAPAD. Disclosure of Interests: : Perrine Dusser: None declared, Chrystelle Hascoet: None declared, Isabelle Koné-Paut Grant/research support from: SOBI has supported drug product (anakinra) for the presented study, Consultant for: SOBI, Novartis, Pfizer, Abbvie, UCB, CHUGAI, ROCHE, Linda Rossi-Semerano Grant/research support from: Roche